Eric Schwimmer Dictionary of Honduran Colloquialisms, Idioms and Slang - Fuenzalida, Mauricio; Ríos Licona, Dina (Boletín de Filología, 2004)
Dictionary of Honduran Colloquialisms, Idioms and Slang. Revised and expanded. A Spanish-English dictionary of words and expressions used in written and spoken Spanish in Honduras, plus a list of acronyms, words thatexpress local origin and shortened forms of proper names, 2ª edición. Tegucigalpa, Litografía López, 2004, X + 228 páginas.